Comparing the Effectiveness of the NBR and NDVI Spectral Indicators in Mapping and Estimating the Burned Areas: a Case Study of Umm Al-Taiour and the Forested Area in the Northern Countryside of Lattakia: مقارنة فعالية المؤشرات الطيفية NBR وNDVI في تخريط المناطق المحترقة وتقدير مساحاتها: حالة دراسة لقرية أم الطيور والمنطقة الحراجية في ريف اللاذقية الشمالي - حويجه, روز (Latakia University Journal -Engineering Sciences Series, 2023)
The purpose of this paper is to identify the burnt areas occurred in Umm Al-Taiour and forested area in the northern countryside of Lattakia during the summer of 2020 using remote sensing techniques. The analyzes were based on the changes in two spectral indicators, the Normalized Burn Ration (NBR) and the Normalized Difference Vegetation Index (NDVI) computed using the Landsat 8 and Sentinel 2A satellite imagery. The images used cover the same area at different times from before and after the fire. We first calculated the change in the NBR using the Landsat 8 satellite bands and repeated the same work using the Sentinel 2A satellite bands. The burnt areas were mapped based on the NBR and NDVI changes, their area was calculated and the results were compared. Later, we applied the same methodology to calculate the change NDVI, map the burnt areas, calculate their areas, and compare the results. The results showed that the use of the NBR indicator is more effective in mapping fires than the NDVI one, whereby an error matrix was generated for the two tested indicators, and the values ​​indicating the image classification accuracy showing burnt and unburned areas were calculated (User Accuracy, Product Accuracy, Over all Accuracy and kappa coefficient). These parameters revealed the high accuracy of the results that can be achieved by the NBR indicator.